2020
DOI: 10.5194/esurf-8-221-2020
|View full text |Cite
|
Sign up to set email alerts
|

Hillslope denudation and morphologic response to a rock uplift gradient

Abstract: Abstract. Documenting the spatial variability of tectonic processes from topography is routinely undertaken through the analysis of river profiles, since a direct relationship between fluvial gradient and rock uplift has been identified by incision models. Similarly, theoretical formulations of hillslope profiles predict a strong dependence on their base-level lowering rate, which in most situations is set by channel incision. However, the reduced sensitivity of near-threshold hillslopes and the limited availa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 113 publications
3
14
0
Order By: Relevance
“…Combining the analysis of detailed high-resolution hillslope morphometry with TCN data is a promising way to investigate landscape dynamics but has been used only in a limited number of situations (DiBiase et al, 2012;Godard et al, 2019Godard et al, , 2020Hurst et al, 2012).…”
Section: Implications For the Detection Of Transient Evolution In Landscapesmentioning
confidence: 99%
“…Combining the analysis of detailed high-resolution hillslope morphometry with TCN data is a promising way to investigate landscape dynamics but has been used only in a limited number of situations (DiBiase et al, 2012;Godard et al, 2019Godard et al, , 2020Hurst et al, 2012).…”
Section: Implications For the Detection Of Transient Evolution In Landscapesmentioning
confidence: 99%
“…Data used in this study are available through Codilean et al (2018), Godard et al (2019Godard et al ( , 2020, Grieve et al (2016), Hurst et al (2012), Richardson et al (2019), andRoering et al (2007).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…OR: Oregon Coast Range, OR (Grieve et al, 2016;Roering et al, 2007). VA: Valensole Plateau, Provence, France (Godard et al, 2020) and A2), and thus their dynamics involve significant nonlinear contributions to the hillslope sediment flux, with response times ranging from 10 ka (OR and GM) to several 100s of ka.…”
Section: Ementioning
confidence: 99%
“…First, we are unable to estimate horizontal cumulative displacements due to the lack of preserved offset markers.Besides, it is currently not possible to estimate when and over how long this cumulative slip has been recorded.Nevertheless, this vertical rate is coherent with published slip rates in western Provence. For example,Godard et al (2020) identified similar rock uplift rates in the Digne-Valensole basin only 35 km to the north of Maragrate. There, the authors deduced a ∼0.021 mm/yr differential uplift velocity along a 10 km-transect, which is interpreted as related to active thrusting.…”
mentioning
confidence: 95%
“…years. In addition, morphological evidence of activity along active fault segments is subdued because denudation rates are comparable or faster than fault velocities (about 30-60 mm/ka, Siame et al, 2004;Molliex et al, 2011;Godard et al, 2016;Thomas et al, 2017;Thomas et al, 2018;Godard et al, 2020). This implies that tectonic geomorphic markers tend to be rapidly eroded away and that no single stand-alone method can be used to accurately evaluate seismic deformation.…”
Section: -Introductionmentioning
confidence: 99%